'B' for Brexit or for Belonging?. Issue 1 (February 2019) - Georgiadou, Lorena
In this article, I use my personal experience of being a UK-based EU national and researcher during 'Brexit' as a vehicle to explore how the 'rise of the right' may be affecting qualitative researchers, their practice, and the context in which their inquiry takes place. In particular, I explore the shift in my sense of belonging as a result of the Brexit vote and the impact that this has on my willingness to remain in Britain and on my research practice. I conceptualise 'belonging' as fluid and relational, and I highlight the central role that 'welcoming the other' can play in facilitating such processes. This then forms the foundation of my exploration of what I think we, as qualitative researchers, can do for our communities as a response to the recent political developments discussed in this special issue.